2020
DOI: 10.52570/nesr.dgac2020.sr0201
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns during Pregnancy and Gestational Weight Gain: A Systematic Review

Abstract: Conclusion statements drawn as part of this systematic review describe the state of science related to the specific question examined. Conclusion statements do not draw implications, and should not be interpreted as dietary guidance. This portfolio provides the complete documentation for this systematic review. A summary of this review is included in the 2020 Advisory Committee's Scientific Report available at www.DietaryGuidelines.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…In this regard, it has been observed that fruit, vegetables, and cereals are consumed less and less, while the consumption of meat, dairy and sugary products has increased in recent times [28,30]. It poses a concern because it may result in excessive weight gain and an increased risk of several pregnancy complications, such as gestational diabetes and hypertension [31,32]. On the other hand, the traditional Polish diet tends to be rich in meat, which could explain the higher protein intake among participating Polish pregnant women compared to Spanish participants [33].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been observed that fruit, vegetables, and cereals are consumed less and less, while the consumption of meat, dairy and sugary products has increased in recent times [28,30]. It poses a concern because it may result in excessive weight gain and an increased risk of several pregnancy complications, such as gestational diabetes and hypertension [31,32]. On the other hand, the traditional Polish diet tends to be rich in meat, which could explain the higher protein intake among participating Polish pregnant women compared to Spanish participants [33].…”
Section: Discussionmentioning
confidence: 99%
“…This approach allows to investigate the complexity of these behaviors, their synergistic and potentially deleterious effects 19 . Studies aiming identify patterns of behaviors in pregnant women focused exclusively on dietary patterns, while some of them have included physical activity as an exposure variable and not combined with food consumption to identified EBRB 24,25 . While few studies evaluated data driven food patterns in relation to FI 26,27 , from our knowledge, there are no studies focused on EBRB and FI in pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…We collected data on dietary supplement usage and found that infants only used supplements containing vitamin D and iron, without including the key components of PLs and LCPUFAs. Additionally, there is limited evidence suggesting that supplementing with omega-3 fatty acids during pregnancy may have a positive impact on cognitive development in children (38). Our study reviewed supplementation during the 12 weeks prior to delivery.…”
Section: Discussionmentioning
confidence: 99%